Genome‐scale metabolic modeling reveals key features of a minimal gene set - Jean‐Christophe Lachance; Dominick Matteau; Joëlle Brodeur; Colton J Lloyd; Nathan Mih; Zachary A King; Thomas F Knight; Adam M Feist; Jonathan M Monk; Bernhard O Palsson; Pierre‐Étienne Jacques; Sébastien Rodrigue (Molecular Systems Biology)
Abstract Mesoplasma florum, a fast‐growing near‐minimal organism, is a compelling model to explore rational genome designs. Using sequence and structural homology, the set of metabolic functions its genome encodes was identified, allowing the reconstruction of a metabolic network representing ˜ 30% of its protein‐coding genes. Growth medium simplification enabled substrate uptake and product secretion rate quantification which, along with experimental biomass composition, were integrated as species‐specific constraints to produce the functional iJL208 genome‐scale model (GEM) of metabolism. Genome‐wide expression and essentiality datasets as well as growth data on various carbohydrates were used to validate and refine iJL208. Discrepancies between model predictions and observations were mechanistically explained using protein structures and network analysis. iJL208 was also used to propose an in silico reduced genome. Comparing this prediction to the minimal cell JCVI‐syn3.0 and its parent JCVI‐syn1.0 revealed key features of a minimal gene set. iJL208 is a stepping‐stone toward model‐driven whole‐genome engineering.